Evaluation of solid waste management at Pamanukan Main Market, Subang - Nuraini, Vivi; Sarto; Wiranto (BKM Public Health and Community Medicine, 2021)
Purpose: Markets are potential sources of increased waste production, especially after daily activities and settlements. Proper waste management in markets is essential to prevent environmental and public health issues. This study aims to evaluate the waste management practices at Pasar Induk (main market), Pamanukan, based on four management aspects: planning, organizing, actuating, and monitoring. Methods: This qualitative study used a case study approach. The number of informants in this study was 7, selected using the purposive sampling technique. The study was done in April-June 2021. Results: Pasar Induk Pamanukan lacks a work plan and SOP for waste management. Human resources and infrastructure facilities owned by Pasar Induk Pamanukan are insufficient for effective waste management. In addition, there is no official coordination between the TPS Pamanukan and the market manager. Enforcement of waste management at the Pasar Induk Pamanukan uses collection, transportation, and disposal techniques. There's no socialization for waste management to the traders. The market manager has abandoned the evaluation of waste management performance at Pasar Induk Pamanukan, and no improvement efforts have been made. Conclusion: The waste management at Pasar Induk Pamanukan, based on the management aspects of planning, organizing, actuating, and controlling, has not been fully implemented or well managed.